Multicultural Education Learning Methods for Early Childhood, Elementary School, and Middle School - Shofwan, Arif Muzayin (PT. Riset Press International, 2025)
Multicultural education learning methods for early childhood, elementary school students, and junior high school students should be applied appropriately to achieve the expected goals. This qualitative research with a literature study will discuss these learning methods. The data analysis technique uses content analysis by sorting things that are in accordance with the focus and objectives of the study. This study produced the following findings. First, the multicultural education learning method that can be implemented in early childhood and lower elementary school students (1, 2, 3) is the contribution method. Second, the multicultural education learning method that can be implemented in upper elementary school students (4, 5, 6) and junior high school is the additive method. Third, several other learning methods can be chosen for the implementation of multicultural education for students, including transformation method, social action method, habituation method, role model method, reward method, punishment method, lecture method, question and answer method, discussion method, deliberation method, seminar method, forum method, assignment and recitation method, demonstration method, experimental method, sociodrama and role-playing method, group work method, study visit method, dictation method, unit method, problem-solving method, programmed teaching method, module method, and so on.